A Modified SPH Method for Dynamic Failure Simulation of Heterogeneous Material. (22nd April 2014) - Ma, G. W.; Wang, Q. S.; Yi, X. W.; Wang, X. J.
Abstract : A modified smoothed particle hydrodynamics (SPH) method is applied to simulate the failure process of heterogeneous materials. An elastoplastic damage model based on an extension form of the unified twin shear strength (UTSS) criterion is adopted. Polycrystalline modeling is introduced to generate the artificial microstructure of specimen for the dynamic simulation of Brazilian splitting test and uniaxial compression test. The strain rate effect on the predicted dynamic tensile and compressive strength is discussed. The final failure patterns and the dynamic strength increments demonstrate good agreements with experimental results. It is illustrated that the polycrystalline modeling approach combined with the SPH method is promising to simulate more complex failure process of heterogeneous materials.